2017
DOI: 10.1038/cddis.2017.503
|View full text |Cite
|
Sign up to set email alerts
|

The lncRNA TUG1 modulates proliferation in trophoblast cells via epigenetic suppression of RND3

Abstract: Due to limited treatment options, pre-eclampsia (PE) is associated with fetal perinatal and maternal morbidity and mortality. During the causes of PE, failure of uterine spiral artery remodeling which might be related to functioning abnormally of trophoblast cells, result in the occurrence and progression of PE. Recently, abnormal expression of long non-coding RNAs (lncRNAs), as imperative regulators involved in human diseases progression (included PE), which has been indicated by increasing evidence. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
105
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 35 publications
(39 reference statements)
4
105
2
Order By: Relevance
“…The lncRNA taurine‐up‐regulated gene 1 (TUG1), a ~7.1 kb highly conserved lncRNA, was originally identified in taurine‐treated retinal cells. TUG1 has been reported to play critical roles in the progression of many human diseases, such as cancer, aortic valve calcification and pre‐eclampsia . Indeed, TUG1 can regulate gene expression via diverse mechanisms during various biological processes, including inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA taurine‐up‐regulated gene 1 (TUG1), a ~7.1 kb highly conserved lncRNA, was originally identified in taurine‐treated retinal cells. TUG1 has been reported to play critical roles in the progression of many human diseases, such as cancer, aortic valve calcification and pre‐eclampsia . Indeed, TUG1 can regulate gene expression via diverse mechanisms during various biological processes, including inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…TUG1 has been reported to play critical roles in the progression of many human diseases, such as cancer, aortic valve calcification and pre-eclampsia. [8][9][10] Indeed, TUG1 can regulate gene expression via diverse mechanisms during various biological processes, including inflammatory response. Overexpression of TUG1 has been shown to protect the mouse liver against cold-induced injury by inhibiting apoptosis and inflammation, 11 whereas TUG1 knockdown inhibits hyperlipidaemia, decreases inflammatory response and alleviates atherosclerotic lesions.…”
mentioning
confidence: 99%
“…13 Down-regulation of Nudt21 expression in cells has been reported to lead to changes in alternative poly(A) site utilization for several somatic mRNAs. 28 In this study, we investigated the mechanistic basis for F I G U R E 6 EZH2 is important for trophoblast growth and migration and endothelial cell tube formation. 28 In this study, we investigated the mechanistic basis for F I G U R E 6 EZH2 is important for trophoblast growth and migration and endothelial cell tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 Many studies have established that Ezh2 acts as a suppressor of RNA transcription through H3K27me3, include in PE. 28 In this study, we investigated the mechanistic basis for the marked increase in NUDT21 expression in the placentas of pregnant women with PE compared with normal pregnancies. Our research confirmed the interaction between EZH2 and NUDT21 and showed that this interaction plays an important role in the crosstalk between APA and miRNA-mediated gene silencing in PE.…”
Section: Discussionmentioning
confidence: 99%
“…Genome‐wide lncRNAs expression patterns indicate numerous lncRNAs extensively expressed in pre‐eclampsia. Previous studies have reported that different expression of lncRNAs in pre‐eclampsia is related to multiple pathways, including trophoblast invasion (Long et al, ), autophagy (Gao et al, ), apoptosis (Song et al, ; Xu et al, ; Zou & Sun, ), proliferation (Cao et al, ; Li et al, ; Xu et al, ), migration, and angiogenesis (Chen et al, ; Yu et al, ; Zhang et al, ). Circular RNAs (circRNAs), as one type of ncRNAs, have been demonstrated to function as a potential regulator of other RNAs transcription like microRNAs (miRNAs).…”
Section: Introductionmentioning
confidence: 99%